Domestic Waste Management Strategy through Realization of School Waste Banks towards Students Scientific Behavior - Sutisno, Aliet Noorhayati; Novianawati, Noor; Hidayatullah, Muhammad Arif Syarif (International Journal of Educational Qualitative Quantitative Research, 2023)
The inability to read the opportunities of the dilemma of the distribution of waste in the environment in relation to the needs of the educational transmission period in the post-pandemic era as it is today leads to our limitations in meeting the needs of educational efforts and strategies in various challenges of the times. This study aims to present educational transmission efforts and strategies for handling waste distribution in the post-pandemic era which is an innovative educational approach towards sustainable human and natural resource development based on an economic-socio-cultural basis. The method is descriptive quantitative that was conducted at one of the public schools elementary from  August until November of the 2021/2022 academic year. The sample is 150 students from 1, 2, and 3-grade elementary schools. The results found in the field are that through the realization of the school waste bank regarding the regulation of implementing waste sorting from home and then proceeding to deposit waste to the school waste bank this strategy initiates scientific practice towards the scientific behavior of students. The contribution of this research is instilling good behavior from an early age, and it is hoped that good habits will emerge and contribute to environmental sustainability.